Immunomorphologic Manifestations in Mice Liver Infected with Influenza A/H5N1, A/Goose/Krasnoozerskoye/627/05 Strain - Oxana V. Potapova; Tatyana V. Sharkova; Vyacheslav A. Shkurupiy; Alexander M. Shestopalov (Clinical and Developmental Immunology)
Highly pathogenic avian influenza H5N1 (HPAI H5N1) viruses can infect mammals, including humans, causing severe systemic disease with the inhibition of the immune system and a high mortality rate. In conditions of lymphoid tissue depletion, the liver plays an important role in host defence against viruses. The changes in mice liver infected with HPAI H5N1 virus A/goose/Krasnoozerskoye/627/05 have been studied. It has been shown that the virus persistence in the liver leads to the expression of proinflammatory cytokines (TNF-α, IL-6) and intracellular proteases (lysozyme, cathepsin D, and myeloperoxidase) by Kupffer cells. Defective antiviral response exacerbates destructive processes in the liver accelerating the development of liver failure.